Malay-English code-mixing insertion: why 'lepaking' in preference to 'hanging out'? - Anuar, Azu Farhana; Paramasivam, Shamala; Ismail, Md Jais (Quantum Academic Publisher, 2020)
This study scrutinized the current media language culture of code-mixing insertion practice of English morpheme (-ing) into Malay lexical item (lepak) by Malaysians on Facebook. A collection of 227 Facebook postings of the usage of ‘lepaking’, where base language of the online postings is Malay, from January to January 2020 to August 2020, were analyzed to investigate on the reasons of ‘lepaking’ instead of ‘hanging out’ utilized by Malaysians on Facebook. This study shadowed Muysken’s (2000) typology of code-mixing insertion which defines ‘the insertion a well-defined chunk of language B into a sentence or word that otherwise belongs to language A’ and further operationalized by using "socially-realistic linguistics” theory of Kachru, Halliday and Firthian is to identify the reasons why ‘lepaking’ in preference to ‘hanging out’. The finding acknowledged a new phenomenon of code-mixing insertion since the ‘chunk’ inserted was in a form of morpheme (-ing), not a complete word. The reasons of the use of ‘lepaking’ identified were: a) Role identification: social, registral, educational, (b) Style identification: the language trend and (c) The yearning to clarify and interpret: the speaker’s attitude and relationship with other persons and the vice versa. In conclusion, ‘lepaking’ is an identification of language fashion of ‘New Englishization’ and it emerges when co-relationship occurs between speaker, linguistic forms and language function.